A descriptive survey of substance use treatment facilities in Uasin Gishu County Kenya - Florence Jaguga; Matthew Turissini; Julius Barasa; Mercy Kimaiyo; Joash Araka; Lily Okeyo; Edith Kwobah (BMC, 2022)
Abstract Background Substance use disorders are a major problem in Uasin Gishu County, Kenya. The objective of this study was to describe the existing resources within substance use treatment facilities in the County, with the aim of guiding policy and interventions. Methods This was a cross-sectional study. We collected data from six substance use treatment facilities within Uasin Gishu County between August and November 2021. We used a researcher-designed questionnaire to collect information on: availability of in-patient and out-patient services; facility ownership (private-for-profit vs government-run); bed capacity; mode of payment for services; cost of services; availability of medicines for substance use treatment; and staffing characteristics. Descriptive statistics were used to summarize the data. Results One facility was run by the National government and the rest were private-for-profit. Uasin Gishu County government had no substance use treatment facility of its own. The total number of beds available within the six facilities was 174 against a population of 1.1 million. All six facilities had stocked at least one medication for substance use disorder treatment. None of the facilities had buprenorphine, buprenorphine naloxone, or methadone. Out-of pocket was the most common mode of payment for services with patients paying using this mode in all the six facilities. Only one facility was accredited by the National Hospital Insurance Fund (NHIF). All facilities had at least one certified addiction counselor and at least one psychologist. Half of the facilities did not have a nurse and two did not have a doctor. The qualification held by most staff was addiction counseling with 41.3% of them having achieved this qualification. Conclusion The facilities were well staffed with psychologists and addiction counselors. Gaps were found as regards bed capacity, use of pharmacotherapy, insurance coverage and availability of nursing staff and doctors. We recommend that the County government in collaboration with key stakeholders invests in substance use treatment in order to address the high burden of substance use disorders in Uasin Gishu County.